A critical review on biochar-based engineered hierarchical porous carbon for capacitive charge storage. (July 2021) - Cuong, Dinh Viet; Matsagar, Babasaheb M.; Lee, Mengshan; Hossain, Md. Shahriar A.; Yamauchi, Yusuke; Vithanage, Meththika; Sarkar, Binoy; Ok, Yong Sik; Wu, Kevin C.-W.; Hou, Chia-Hung
Abstract: Hierarchical porous carbon (HPC) has attracted increasing research interest for energy and environmental applications. HPC is conventionally fabricated by activated carbon, which potentially causes hidden environmental burdens. To overcome this issue, biochar, a promising renewable precursor, offers an attractive raw material substitute and has already been explored for the preparation of low-cost HPC. Recent studies have demonstrated that HPC exhibited great applications in capacitive energy storage, owning to its easily tuned physicochemical and electrochemical properties. Besides, biochar-based HPC with a three-dimensional (3D) interconnected controllable pore structure, high specific surface area (SSA), and pore volume (PV) can provide smaller resistance and shorter diffusion pathways for the transport of ions. Importantly, most recent research efforts have been made on the synthesis of biochar-based engineered hierarchical porous carbons (EHPCs) from biomass/biochar or developed from the HPC. A templating technique, heteroatom, and metal oxides doping have been applied to develop the biochar-based EHPC to improve 3D pore structure or/and expose abundant active sites and subsequently enhance the capacitive charge storage performance. In this review, recent advances in the applications of biochar-based HPC or EHPC for capacitive charge storage, e.g., capacitive deionization (CDI) and a supercapacitor (SC) are summarized and discussed. This review concludes with several perspectives to provide possible future research directions for the preparation and applications of biochar-based EHPC for capacitive charge storage. Graphical abstract: Image 1 Highlights: Biochar-based HPC is an efficient sustainable material for capacitive charge storage. Biochar-based HPC contains a 3D pore structure and abundant functional groups. Engineered HPC can be obtained with controlled porosity and surface modification. Electrode architecture design can ensure the fast transport of ions. Heteroatom and electroactive particle doping can enhance charge storage capability.